2014
DOI: 10.1177/1524838014561269
|View full text |Cite
|
Sign up to set email alerts
|

Problem Gambling and Intimate Partner Violence

Abstract: This study provides a systematic review of the empirical evidence related to the association between problem gambling and intimate partner violence (IPV). We identified 14 available studies in the systematic search (8 for victimisation only, 4 for perpetration only and 2 for both victimisation and perpetration). Although there were some equivocal findings, we found that most of the available research suggests that there is a significant relationship between problem gambling and being a victim of IPV. There was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
110
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 53 publications
9
110
0
1
Order By: Relevance
“…Most research to date has used treatment-seeking samples or convenience samples with an explicit focus on problem gamblers [21] and alcohol and drug research seldom has a gambling focus [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Most research to date has used treatment-seeking samples or convenience samples with an explicit focus on problem gamblers [21] and alcohol and drug research seldom has a gambling focus [45].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these problem and/or pathological gamblers are not representative of problem gamblers in the community, and a broader range of gamblers is seldom considered [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, among Veterans, gambling has been associated with suicidal ideation and attempts (Kausch, 2003a, 2003b; Kausch, 2004), substance use and SUDs (e.g., alcohol use and use disorders; Desai et al, 2004; Edens & Rosenheck, 2012; Kausch, 2003a; Potenza, Maciejewski, & Mazure, 2006; Rash, Weinstock, & Van Patten, 2016; Westermeyer et al, 2005; Westermeyer et al, 2008), and with psychiatric disorders (e.g., depression, anxiety; Edens & Rosenheck, 2012; Westermeyer et al, 2005; Westermeyer et al, 2008). Similarly, violence and aggression (e.g., partner and non-partner violence; aggressive behavior; family violence) have been associated with both pathological and problem gambling among civilians (Parke & Griffiths, 2004; Korman et al, 2008; Goldstein et al, 2009; Adachi & Willoughby, 2013; Suomi et al, 2013; Roberts et al, 2016; Dowling et al, 2014; Dowling et al, 2016), and data from a nationally representative sample in the United States (US) showed that the odds of violent behavior are significantly greater among individuals with gambling problems (Pulay et al, 2008). Further evaluation contextualizing the co-occurrence of violence with gambling and in SUD samples, particularly among Veterans, could inform clinical efforts with such patients.…”
Section: Introductionmentioning
confidence: 99%